Bipolar Androgen Therapy for Men With Androgen Ablation Naïve Prostate Cancer: Results From the Phase II BATMAN Study. Issue 13 (24th June 2016) - Schweizer, Michael T.; Wang, Hao; Luber, Brandon; Nadal, Rosa; Spitz, Avery; Rosen, D. Marc; Cao, Haiyi; Antonarakis, Emmanuel S.; Eisenberger, Mario A.; Carducci, Michael A.; Paller, Channing; Denmeade, Samuel R.
Abstract : BACKGROUND: We have previously documented a paradoxical anti‐tumor effect when castration‐resistant prostate cancer patients were treated with intermittent, high‐dose testosterone (i.e., Bipolar Androgen Therapy; BAT). Because, an adaptive increase in androgen receptor expression following chronic androgen deprivation therapy (ADT) may underlie this effect, we tested whether men with hormone‐sensitive (HS) prostate cancer (PC) would also respond to BAT if given following a 6‐month ADT lead‐in. METHODS: Asymptomatic HS PC patients with low metastatic burden or non‐metastatic biochemically recurrent disease were enrolled. Following 6‐month of ADT, those with a PSA <4 ng/ml went on to receive alternating 3‐month cycles of BAT and ADT. BAT was administered as intramuscular testosterone (T) cypionate or enanthate 400 mg on Days (D) 1, 29, and 57. ADT was continued throughout the study to allow rapid cycling from near castrate to supraphysiologic range T following T injections. The primary endpoint was the percent of patients with a PSA <4 ng/ml after 18 months. Secondary endpoints included radiographic response and quality of life (QoL). RESULTS: Twenty‐nine of 33 patients received BAT following the ADT lead‐in. The primary endpoint was met, with 17/29 men (59%, 90% confidence interval: 42–74%) having a PSA <4 ng/ml at 18 months. Ten patients receiving BAT had RECIST evaluable disease, and eight (80%) objective responses were observed (four complete; four partial). Three patients progressed per RECIST criteria and three had unconfirmed progression on bone scan. Men treated with 6‐month of ADT had improved QoL following the first cycle of BAT as measured by the SF‐36, FACT‐P, and IIEF surveys. CONCLUSIONS: BAT demonstrated preliminary efficacy in men with HS PC following 6‐month of ADT. BAT may improve QoL in men treated with ADT. Prostate 76:1218–1226, 2016 . © 2016 Wiley Periodicals, Inc.